Development And Evaluation Of Matrix Controlled Release Formulations Of Ketoprofen - Khan, Jiyauddin (2010)
The present study was conducted to investigate the suitability of various hydrophilic and hydrophobic polymers or their combination, as matrix forming materials for the development of a controlled release tablet formulation of ketoprofen with in vitro and in vivo performance comparable to that of the marketed preparation Apo-Keto SR® tablets. In this regard a number of matrix controlled release formulations of ketoprofen tablets were developed using different hydrophilic, hydrophobic and mixtures of both polymeric materials. All the formulations were prepared by direct compression method. Their in vitro dissolution profiles were compared to that of the commercially available reference product Apo-Keto SR® tablet. Similarity factor (f2), values between test formulations and reference product were also calculated to select the optimum formulation. Out of all the matrix formulations studied, tablets containing 20% HPC (GXF) as matrix former showed comparable dissolution profile to that of the reference. The f2 value between reference and matrix tablets with 20% HPC (GXF) was 78.0%, and hence it was selected for further investigation. The drug release from reference and matrix with 20% HPC (GXF) formulation was governed by both diffusion and erosion (anomalous) mechanism as per Korsmeyer-Peppas equation. Moreover, the optimized formulation was found to be stable for a period of 12 months upon storage at 25ºC of room temperature for a long term of stability.